Intraosseous uric acid tumor without joint involvement: case report - Valloto Junior, Elcio; Penna, Valter; Guimarães, Vinícius Medina; Pozzebon, Vinícius Dino; Araújo, Mariana Oliveira de (Journal of the Foot & Ankle, 2021)
We report an unusual case of extra-articular gouty tophus in the left medial malleolus. A 33-year-old man with a previous diagnosis of chronic gout presented with mild, non-disabling ankle pain associated with gout attacks. Imaging and histopathologic findings were inconclusive. The tumor was surgically resected, and the cavity was filled with methyl methacrylate. Histopathology confirmed the diagnosis in a sample collected intraoperatively. Giant cell tumor and bone cyst were ruled out. The patient had a good postoperative outcome. Level of Evidence V; Therapeutic Study; Expert Opinion.